Solid electrolyte, solid-state battery and method for producing solid-state battery

A solid electrolyte with reduced Ge content and optimized composition of Li, Al, and Sn enhances Li ion conductivity and sinterability, addressing cost and stability issues in solid-state batteries.

JP2024174291APending Publication Date: 2024-12-17FDK CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023092040
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-05
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Conventional solid electrolytes for solid-state batteries contain rare and expensive elements like Ge, leading to high material and environmental costs, and often face challenges in sinterability and Li ion conductivity due to chemical reactions with electrode active materials.

Method used

A solid electrolyte composed of Li, Al, Sn, and P with a polyphosphoric acid skeleton, where the Ge composition is less than the Sn composition, specifically formulated as Li1+xAlxSn2-x-y(PO4)3, which reduces Ge content and enhances sinterability and Li ion conductivity.

Benefits of technology

This composition achieves high Li ion conductivity, reduces material costs by half, and ensures stable operation by minimizing reactions with electrode materials, making it suitable for high-energy density and safe solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024174291000001_ABST
    Figure 2024174291000001_ABST
Patent Text Reader

Abstract

To provide a cost-effective solid electrolyte.SOLUTION: A solid electrolyte contains Li, Al, Sn, Ge and P, bears a polyphosphoric acid skeleton, and offers Li ion conductivity, with the Ge composition being smaller than the Sn composition. In the solid electrolyte, Ge content is reduced, achieving a high degree of cost-effectiveness. Such a solid electrolyte is used to produce a solid-state battery 1 including a positive electrode layer 11 and a negative electrode layer 12, and an electrolyte layer 13 located between them. The solid electrolyte is represented by the formula Li1+xAlxSnyGe2-x-y(PO4)3. For example, Sn composition y and Ge composition z=2-x-y are within the range of 0.13≤z / (y+z)≤0.33, and the Al composition x is within the range of 0.2≤x≤0.5.SELECTED DRAWING: Figure 6
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a solid electrolyte, a solid-state battery, and a method for producing a solid-state battery. [Background technology]

[0002] A solid-state battery using a solid electrolyte as an electrolyte is known. For example, the solid electrolyte contains Li, Al, Ge, and P and has the composition formula Li 1+x Al x Ge 2-x A technology using a solid electrolyte such as a LAGP-based material represented by (PO4)3 is known (Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2015-69843 A Summary of the Invention [Problem to be solved by the invention]

[0004] If a solid electrolyte for a solid-state battery contains a relatively large amount of Ge, which is a rare and expensive element, the cost of the solid electrolyte increases, which in turn increases the cost of the solid-state battery that uses the solid electrolyte.

[0005] In one aspect, the present invention aims to realize a solid electrolyte at reduced cost. [Means for solving the problem]

[0006] In one embodiment, there is provided a solid electrolyte comprising Li, Al, Sn, Ge and P, having a polyphosphate skeleton and Li-ion conductivity, wherein the Ge composition is smaller than the Sn composition.

[0007] In another aspect, there is provided a solid-state battery including the solid electrolyte as described above and a method for producing the solid-state battery. Effect of the Invention

[0008] On the one hand, it will be possible to realize solid electrolytes at reduced cost. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 shows the results of X-ray diffraction measurement of Li1+xAlxSnyGe2-xy(PO4)3. [Diagram 2] FIG. 1 shows the results of X-ray diffraction measurement of a mixed powder of Li2CoP2O7 and Li1+xAlxSnyGe2-xy(PO4)3 after sintering. [Diagram 3] FIG. 1 is a diagram showing the relationship between ionic conductivity and composition of Li1+xAlxSnyGe2-xy(PO4)3. [Figure 4] FIG. 1 is a diagram showing the relationship between the Al composition x, ionic conductivity, and density of Li1+xAlxSnyGe2-xy(PO4)3. [Diagram 5] FIG. 1 is a diagram showing the composition search procedure for Li1+xAlxSnyGe2-xy(PO4)3. [Figure 6] 1A to 1C are diagrams illustrating an example of a method for manufacturing a solid-state battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Li-ion secondary batteries are used in many electronic devices, but one of the drawbacks of these batteries is that the electrolyte is highly flammable, which can lead to the risk of ignition or combustion. For this reason, it has been necessary to take safety into consideration when using them, such as avoiding use at high temperatures and applying high voltages for long periods of time. Solid-state batteries are batteries in which the electrolyte in the battery has been replaced with a Li-ion conductive solid electrolyte. By using a solid electrolyte, it is possible to prevent not only fire, but also evaporation, decomposition, and leakage. In addition, by using a solid electrolyte, it is possible to use high-performance electrode materials that could not be used with electrolytes, and this is expected to lead to higher capacity, higher energy density, longer life, and lower costs.

[0011] Conventionally, oxide-based solid electrolytes have been known as one type of solid electrolyte for solid-state batteries. For example, polyanion-type solid electrolytes having a NASICON (Na superionic conductor) structure have been known. One such solid electrolyte is Li 1.5 Al 0.5 Ge 1.5 Li 1+x Al x Ge 2-x There is LAGP represented by (PO4)3. 2 / 3-x Li 3x Perovskite-type solid electrolytes such as TiO3, Li7La3Zr2O 12 Garnet-type solid electrolytes based on the above and substituted with various elements are also known.

[0012] However, conventional solid electrolytes often contain rare and expensive elements such as Ge, Ti, and La, or elements that are harmful or have a high environmental impact. For example, in a solid-state battery using LAGP as a solid electrolyte, when Li2CoP2O7 (hereinafter also referred to as "LCPO") is used as the positive electrode active material, LAGP is used as the solid electrolyte, and TiO2 is used as the negative electrode active material, the material cost of Ge accounts for more than 90% of the total material cost. Therefore, if the Ge content of the solid electrolyte can be reduced, the cost can be reduced, and further the cost of the solid-state battery using it can be reduced. In addition, if the Ge content of the solid electrolyte can be reduced, it can also contribute to reducing the environmental impact.

[0013] In view of the above, in this embodiment, a solid electrolyte for use in a solid-state battery is provided that has the following configuration. That is, a solid electrolyte containing Li, Al, Sn, Ge, and P, having a polyphosphate backbone, and having Li-ion conductivity is provided, wherein the Ge composition is smaller than the Sn composition. The solid electrolyte according to this embodiment contains Sn together with Ge and has a configuration in which the Ge composition is smaller than the Sn composition. Thus, compared with the conventional LAGP, only Ge among Ge and Sn is contained, that is, the Ge content in the solid electrolyte is reduced, and the material cost is reduced. As a result, the cost of the solid electrolyte is suppressed, and further, the cost of a solid battery using the solid electrolyte is suppressed.

[0014] The solid electrolyte according to the embodiment has a composition formula of Li 1+x Al x Sn y Ge 2-x-y (PO4)3 and is a solid electrolyte having a polyphosphate backbone. The solid electrolyte represented by such a composition formula is also referred to as "LASGP" hereinafter. Assuming the Ge composition 2 - x - y = z, when the Ge composition z of the solid electrolyte is smaller than the Sn composition y, that is, when it has a relationship of z < y or z / y < 1, the Ge content is reduced by more than half compared with the conventional LAGP, and the cost is greatly suppressed.

[0015] Here, for the solid electrolyte LASGP represented by the composition formula Li 1+x Al x Sn y Ge 2-x-y (PO4)3, it is preferable that there is a relationship of 0.13 ≦ z / (y + z) ≦ 0.33 between the Sn composition y and the Ge composition z (= 2 - x - y). In this case, it is more preferable that LASGP has a composition ratio of y:z = 4:1 or z / y < 0.25, or a relationship of z / (y + z) = 0.2 between the Sn composition y and the Ge composition z. According to LASGP having such a relationship for the Sn composition y and the Ge composition z (= 2 - x - y), a solid electrolyte showing high Li-ion conductivity while reducing the Ge content is realized. For example, when the Ge content is reduced to 20% of the conventional LAGP, the material cost of the solid battery can be suppressed to about one-fifth.

[0016] Also, for the composition formula Li 1+xAl x Sn y Ge 2-x-y In the LASGP, which is a solid electrolyte represented by (PO4)3, the Al composition x is preferably in the range of 0.2≦x≦0.5. According to the LASGP having such a relationship for the Al composition x, it is possible to realize a solid electrolyte that exhibits good sinterability, obtains a dense sintered body in the sintering process, and exhibits high Li-ion conductivity even after the sintering process.

[0017] In recent years, the specifications required for batteries have become more diverse, and there is growing interest in higher energy density and safety in particular. Solid-state batteries are highly safe and can be used in low to high temperature environments, so there are high expectations for their practical use. It is desirable for the solid electrolyte used in solid-state batteries to have high Li-ion conductivity. However, in solid-state batteries using solid electrolytes, a sintering process is generally performed during production, but if the solid electrolyte is difficult to sinter, it is difficult to densify it, and the Li-ion conductivity inherent to the bulk may not be exhibited due to the effects of grain boundary resistance, etc. In addition, depending on the composition of the solid electrolyte, a chemical reaction may occur with the active material of the electrodes such as the positive electrode during sintering, causing the active material and solid electrolyte to decompose, making it impossible to obtain a solid-state battery that operates well.

[0018] In contrast, the composition formula Li 1+x Al x Sn y Ge 2-x-y LASGP represented by (PO4)3, in which the Ge composition 2-xy=z is smaller than the Sn composition y, and in particular, LASGP in which the Sn composition y and the Ge composition z or the Al composition x are adjusted to fall within the above-mentioned range, achieves good sinterability and densification, and achieves high Li-ion conductivity. For example, as described below, conventional LAGP has an ion conductivity of 6.5×10 -5 S / cm (measured by AC impedance at 25°C), whereas the ionic conductivity of the LASGP described above was up to 5.4 × 10 -4 S / cm (measured by AC impedance at 25°C). The above-mentioned LASGP makes it possible to reduce the resistance of solid-state batteries.

[0019] In addition, when conventional solid electrolytes Li2B4O7, Li3BO3, Li5AlO4, and Li4SiO4, as well as their mixed compositions, were sintered together with LCPO, a high-capacity positive electrode active material, it was found that all of them reacted with LCPO and caused it to disappear. On the other hand, it was found that Li3PO4 has low reactivity with LCPO and does not cause it to disappear, but its extremely low Li-ion conductivity makes it difficult to use as a solid electrolyte in solid-state batteries.

[0020] In contrast, in the case of the above-mentioned LASGP, the loss of LCPO was suppressed when sintered together with LCPO, as described below. In addition to LCPO, the loss of LiCoPO4, another type of positive electrode active material, during sintering with LASGP is also suppressed. LASGP can be said to be a material that suppresses the loss of LCPO and the like, is densified due to good sinterability, and exhibits high Li-ion conductivity. With the above-mentioned LASGP, it is possible to realize a high-capacity solid-state battery that takes advantage of the characteristics of LCPO (maximum of approximately 220 mAh / g).

[0021] Hereinafter, an embodiment of the LASGP having the above-mentioned configuration will be described in detail together with a comparative example. LASGP was produced using the following method. The raw materials Li2CO3, Al2O3, SnO2, GeO2, and NH4H2PO4 were mixed in predetermined amounts, and then ball milled after mixing to obtain the target material with a more homogeneous NASICON-type structure. The material was then fired (pre-fired) at 400°C for 3 hours, and crushed again in a ball mill to obtain a precursor powder. This was then formed into pellets and fired in two stages (main firing) at 500°C for 5 hours and then for another 10 hours to obtain the powder with the composition formula Li 1+x Al x Sn y Ge 2-x-y We fabricated LASGP with the formula (PO4)3. We also fabricated one with Al composition x = 0.0.

[0022] The Li1+x Al x Sn y Ge 2-x-y X-ray diffraction (also known as XRD) measurements were performed on (PO4)3. An example of the measurement results is shown in Figure 1. Figure 1 shows Li 1+x Al x Sn y Ge 2-x-y FIG. 1 shows the results of X-ray diffraction measurement of (PO4)3. The Al composition x is set in the range of 0.0≦x≦0.5, and the Sn composition y and Ge composition 2−xy=z are set to z / (y+z)=0.2. 1+x Al x Sn y Ge 2-x-y The results of X-ray diffraction measurements of (PO4)3 are shown.

[0023] From Figure 1, the peaks due to the NASICON-type structure with few impurities were confirmed. The diffraction peaks due to the raw materials did not appear in all compositions, and Li 1+x Al x Sn y Ge 2-x-y It can be seen that (PO4)3 was successfully synthesized. In particular, it can be seen that LiSnGePO crystalline materials without any heterophase were produced at Al compositions of x = 0.3 and x = 0.4. At other Al compositions of x, some peaks indicating the precipitation of heterophases (SnO2, etc.) were observed, but LiSnGePO crystalline materials with good crystallinity were produced overall. 1+x Al x Sn y Ge 2-x-y (PO4)3 has been obtained.

[0024] In addition, the Li 1+x Al x Sn y Ge 2-x-y (PO4)3 was sintered together with LCPO, which is the positive electrode active material, and X-ray diffraction measurements were performed to evaluate the changes in physical properties before and after sintering. An example of the measurement and evaluation results is shown in Figure 2 and Table 1.

[0025] Figure 2 shows LCPO (Li2CoP2O7) and Li 1+x Alx Sn y Ge 2-x-y 2 shows the results of X-ray diffraction measurement of the mixed powder with (PO4)3 after sintering. The sintering was performed in a N2 atmosphere at 600°C. Figure 2 shows the results of X-ray diffraction measurement of the mixed powder with (PO4)3 after sintering. The Al composition x was set in the range of 0.1≦x≦0.5, and the Sn composition y and Ge composition 2-xy=z were set to z / (y+z)=0.2. 1+x Al x Sn y Ge 2-x-y The figure shows the results of X-ray diffraction measurement of the mixed powder of (PO4)3 and LCPO after firing. Figure 2 also shows the results of X-ray diffraction measurement of LCPO.

[0026] Table 1 shows the relationship between LCPO and Li 1+x Al x Sn y Ge 2-x-y The physical properties of the pellets formed from the powder mixture with (PO4)3 before and after sintering are shown in Table 1. The sintering was carried out in a N2 atmosphere at 600°C. Table 1 shows the physical properties of the pellets formed from the powder mixture with (PO4)3 before and after sintering. The sintering was carried out in a N2 atmosphere at 600°C. 1+x Al x Sn y Ge 2-x-y The weight [g], thickness [mm], width [mm], and volume [cm3] of the pellets formed from the mixed powder of (PO4)3 and LCPO before and after sintering 3 ] and density [g / cm 3 ] is shown.

[0027] [Table 1]

[0028] As shown in Figure 2, the X-ray diffraction measurement after firing showed that LCPO and Li 1+x Al x Sn y Ge 2-x-yOnly the peaks derived from (PO4)3 were observed, and the positions of the peaks did not change, indicating that LCPO was maintained without reacting or decomposing before and after firing. From Table 1, although there was a slight change in the color of the pellets before and after firing, there was almost no change in the physical properties listed above. Together with the results of the X-ray diffraction measurements, 1+x Al x Sn y Ge 2-x-y It was confirmed that the reaction between (PO4)3 and LCPO was suppressed.

[0029] Also, Li 1+x Al x Sn y Ge 2-x-y The ionic conductivity of each (PO4)3 composition was measured by the AC impedance method. 1+x Al x Sn y Ge 2-x-y (PO4)3 calcined at 850 °C was used. The ionic conductivity was measured in the frequency range of 1 MHz to 4 Hz, with an amplitude of 100 mV and an electrode area of ​​0.28 cm2. 2 (6 mm diameter disk) and the measurement environment was 25°C or 60°C and a relative humidity of 0% RH. Examples of the measurement results are shown in Tables 2 and 3.

[0030] [Table 2]

[0031] [Table 3]

[0032] Table 2 shows the composition of the constituent elements, ionic conductivity [S / cm], density [g / cm 3 ] and ionic conductivity classification symbol (○ / △ / □). Table 3 shows the composition of the constituent elements, ionic conductivity [S / cm], density [g / cm 3and the classification symbols (◯ / △ / □) of ionic conductivity. Samples No. 1-9 shown in Table 2 correspond to examples, and Samples No. 10-14 shown in Table 3 correspond to comparative examples.

[0033] Li 1+x Al x Sn y Ge 2-x-y The density of (PO4)3 depends on the Sn composition y and the Ge composition 2-xy=z, and is not determined simply by the Al composition x. However, as shown in Table 3, when the Al composition x is less than 0.2, the density is uniformly low regardless of the composition of other elements. 1+x Al x Sn y Ge 2-x-y In order to enhance the sinterability of (PO4)3 and improve the density (densification), it is preferable that the Al composition x is 0.2 or more.

[0034] In Tables 2 and 3, the classification symbols for ionic conductivity are: ionic conductivity of conventional LAGP, 6.5×10 -5 The classification code 〇 indicates that the ionic conductivity is improved over the conventional LAGP (2.0×10 -4 The classification symbol △ denotes ionic conductivity equivalent to that of conventional LAGP (3.9×10 -5 S / cm or more 2.0×10 -4 The classification symbol □ denotes materials with a lower ionic conductivity than conventional LAGP (less than 3.9×10 -5 S / cm).

[0035] Samples No. 10-14 (Table 3) indicated with classification symbol □ have low ionic conductivity, high resistance, and are difficult to operate as batteries, making them difficult to use as solid electrolytes in solid-state batteries. Samples No. 4-9 (Table 2) indicated with classification symbol △ have resistance at the same level as conventional materials, so there is no significant improvement in battery characteristics, but the Ge content is reduced compared to conventional LAGP, reducing costs and making them a viable solid electrolyte for solid-state batteries. Samples No. 1-3 (Table 2) indicated with classification symbol 〇 have ionic conductivity that is more than three times higher than conventional materials, and combined with the cost reduction effect of reducing the Ge content compared to conventional LAGP, they are particularly useful as solid electrolytes for solid-state batteries.

[0036] From Tables 2 and 3, Li 1+x Al x Sn y Ge 2-x-y Among (PO4)3, those with an Al composition x in the range of 0.2≦x≦0.5, and an Sn composition y and a Ge composition z (=2-xy) in the range of 0.13≦z / (y+z)≦0.33 (classification symbols ◯ and △) can be said to be materials that can reduce costs by reducing the Ge content compared to conventional LAGP, and can also function sufficiently as a solid electrolyte for solid-state batteries.

[0037] Figure 3 shows Li 1+x Al x Sn y Ge 2-x-y FIG. 3 shows the relationship between ionic conductivity and composition of (PO4)3. 1+x Al x Sn y Ge 2-x-y On a ternary phase diagram expressed in terms of the Sn:Ge:Al content ratio in (PO4)3, the ionic conductivity classification symbols (○ / △ / □) for samples No. 1-14 shown in Tables 2 and 3 are plotted at positions corresponding to their respective compositions.

[0038] On the phase diagram shown in Fig. 3, ◯ indicates that the ionic conductivity is improved compared to conventional LAGP, and are the plot points of samples No. 1-3, which are classified as ◯ in Table 2. On the phase diagram shown in Fig. 3, △ indicates that the ionic conductivity is approximately the same as conventional LAGP, and are the plot points of samples No. 4-9, which are classified as △ in Table 2. On the phase diagram shown in Fig. 3, □ indicates that the ionic conductivity is lower compared to conventional LAGP, and are the plot points of samples No. 10-14, which are classified as □ in Table 3.

[0039] As shown in Figure 3, the Li 1+x Al x Sn y Ge 2-x-y (PO4)3, that is, all of those indicated by the classification symbols 〇 and △, have an Al composition x in the range of 0.2≦x≦0.5, and an Sn composition y and a Ge composition 2-xy=z in the range of 0.13≦z / (y+z)≦0.33. On the other hand, the Li 1+x Al x Sn y Ge 2-x-y All but one of the (PO4)3 species lie outside the above composition range.

[0040] In the above composition condition of 0.13≦z / (y+z)≦0.33, z / (y+z)=0.2 is synonymous with the ratio of Sn composition y to Ge composition z (=2-xy) being y:z=4:1. Line L1 shown in the phase diagram of FIG. 3 is a line connecting the point that divides the Sn content and Ge content into 4:1 and the apex of the 100% Al content. 1+x Al x Sn y Ge 2-x-y In (PO4)3, the ratio of Sn composition y to Ge composition z (=2-xy) is y:z=4:1, that is, z / (y+z)=0.2. 1+x Al x Sn y Ge 2-x-yIn (PO4)3, higher ionic conductivity was obtained than in the conventional LAGP.

[0041] Li 1+x Al x Sn y Ge 2-x-y The reason why the ionic conductivity increases by setting the Al composition x, the Sn composition y, and the Ge composition z (=2-xy) in the above-mentioned composition ranges in (PO4)3 will be explained below.

[0042] Here, Figure 4 shows Li 1+x Al x Sn y Ge 2-x-y FIG. 4(A) shows the relationship between the Al composition x, ionic conductivity, and density of (PO4)3. 1+x Al x Sn y Ge 2-x-y An example of the relationship between the Al composition x of (PO4)3 and the ionic conductivity [S / cm] is shown in Fig. 4(B). 1+x Al x Sn y Ge 2-x-y Density of (PO4)3 [g / cm 3 An example of the relationship between the ionic conductivity [S / cm] and the ionic conductivity [S / cm] is shown in Fig. 4(C). 1+x Al x Sn y Ge 2-x-y Al composition x and density [g / cm 3 ] is an example of a relationship between

[0043] From Fig. 4(A), Li 1+x Al x Sn y Ge 2-x-y The ionic conductivity of (PO4)3 tends to increase with increasing Al composition x. 1+x Al x Sn y Ge 2-x-y When checking the correlation between density and ionic conductivity of (PO4)3, the ionic conductivity tends to increase as the density increases. From Figure 4(C), Li 1+x Alx Sn y Ge 2-x-y As the Al composition x of (PO4)3 increases, the density tends to increase. From Figures 4(A) to 4(C), it can be explained that the sinterability increases with the increase in the Al composition x, and the density increases to form a dense material, which improves the ionic conductivity.

[0044] On the other hand, when the Al composition x is small, about x = 0.1, the density is low, but the ionic conductivity is significantly improved compared to when no Al is included (Al composition x = 0.0), and it is clear that the addition of Al improves the Li-ion conductivity of the material. The reason for this is thought to be an increase in the carriers involved in Li-ion conduction.

[0045] In other words, Al has two effects of improving Li-ion conductivity: increasing the number of carriers and improving density. 1+x Al x Sn y Ge 2-x-y In (PO4)3, by setting the Al composition x to 0.2 or more, both effects can be obtained. When the Al composition x is set to 0.5 or more, these effects are almost saturated, and conversely, it is difficult for Al to form a solid solution, and it tends to decompose easily at high temperatures. The X-ray diffraction measurement shown in Figure 1 also shows that when the Al composition x is set to 0.5 or more, the precipitation of different phases tends to increase, making it unsuitable as a solid electrolyte for solid-state batteries.

[0046] However, increasing the density by setting the Al composition x in the range of 0.2≦x≦0.5 does not necessarily improve the Li ion conductivity. Looking at Figure 4(B), it can be seen that some materials have low ion conductivity even if their density is high. Looking at the phase diagram in Figure 3, the Li ion conductivity is increased when the Sn composition y and Ge composition 2-xy=z are z / (y+z)=0.2. 1+x Al x Sn y Ge 2-x-y The ionic conductivity is improved in (PO4)3, and as the composition moves away from this condition, the ionic conductivity tends to decrease. 1+x Al x Sny Ge 2-x-y (PO4)3 has a composition of z / (y+z)=0.2. Li with a composition on line L1 1+x Al x Sn y Ge 2-x-y It can be said that all (PO4)3 exhibit high ionic conductivity, and the ionic conductivity tends to decrease as the distance from the line L1 increases. 1+x Al x Sn y Ge 2-x-y In (PO4)3, it can be explained that the ratio of the Sn composition y to the Ge composition z, in addition to the Al composition x, affects the ionic conductivity.

[0047] Li 1+x Al x Sn y Ge 2-x-y (PO4)3 has a NASICON-type crystal structure, but since Ge and Sn exist at the same lattice site, as the Sn content increases, Ge is replaced by Sn. At this time, since the atomic radius of Sn is larger than that of Ge, the lattice spacing around it expands, making it easier for Li ions to pass through, which is thought to have the effect of improving Li ion conductivity. This explains why the Li ion conductivity improves as the Sn composition y increases, but when the Sn composition y increases to a range where the ratio of Sn composition y to Ge composition z (= 2-xy) exceeds y:z = 4:1, Sn cannot be dissolved in the crystal, the crystallinity decreases, and the Li ion conductivity also decreases (Figure 3). Therefore, even if the density is improved by setting the Al composition x in the range of 0.2≦x≦0.5, if the Sn composition y and the Ge composition z (=2−xy) are out of the range of 0.13≦z / (y+z)≦0.33, the original Li-ion conductivity is low, and good characteristics may not be obtained.

[0048] Li of each composition 1+x Al x Sn y Ge 2-x-yWhen the temperature change in ionic conductivity measured with (PO4)3 was summarized, it was confirmed that all compositions followed the Arrhenius law. Although there was no significant difference in the temperature dependence (slope of the graph) between compositions, there was a tendency for the slope to decrease with increasing Al composition x, indicating that the Li-ion conductivity can be optimized by adjusting the Al composition x depending on the temperature range in which the solid-state battery is used.

[0049] In addition, a potential window evaluation test (LSV measurement: linear sweep voltammetry) was performed, and Li 1+x Al x Sn y Ge 2-x-y With (PO4)3, the results were comparable to those of conventional LAGP, and the solid-state battery had Li 1+x Al x Sn y Ge 2-x-y It was found that the voltage range that can be used when (PO4)3 is used is similar to that when conventional LAGP is used. Although the change due to the composition is small, the waveform was most stable and the resistance to high voltages tended to be high when the Al composition x was in the range of 0.25≦x≦0.3.

[0050] From the above, Li 1+x Al x Sn y Ge 2-x-y A solid electrolyte represented by (PO4)3, in particular, Li, in which the Sn composition y and the Ge composition 2-xy=z are in the range of 0.13≦z / (y+z)≦0.33, and the Al composition x is in the range of 0.2≦x≦0.5. 1+x Al x Sn y Ge 2-x-y (PO4)3 realizes a solid electrolyte that is dense and has high Li ion conductivity. 1+x Al x Sn y Ge 2-x-y (PO4)3 reduces the content of rare and expensive Ge compared to conventional LAGP, enabling the realization of a cost-effective solid electrolyte.

[0051] Li 1+x Al x Sny Ge 2-x-y The Li ion conductivity of (PO4)3 is maximum at Al composition x = 0.4, Sn composition y = 1.28, and Ge composition 2-xy = z = 0.32 (x = 0.4, z / (y + z) = 0.2), and decreases as the composition moves away from these values. 1+x Al x Sn y Ge 2-x-y (PO4)3 tends to show high ionic conductivity, especially when z / (y+z)=0.2, and is useful as a solid electrolyte for solid-state batteries. However, other compositions also have useful characteristics in terms of reduced Ge content, temperature dependency, and electrochemical stability (stability to high voltage), and the composition can be freely selected depending on the characteristics required for solid-state batteries.

[0052] Furthermore, Li 1+x Al x Sn y Ge 2-x-y The composition of (PO4)3 was obtained using AI (Artificial Interigence) and simulation. Figure 5 shows Li 1+x Al x Sn y Ge 2-x-y FIG. 1 is a diagram showing the composition search procedure for (PO4)3.

[0053] First, a group of elements that can be used in the solid electrolyte was selected (Step S1). For the selected group of elements, a structural model was created assuming that the element would combine with LCPO, the positive electrode active material, or decompose LCPO, and the presence or absence of reactivity with LCPO was determined by comparing the energy before and after the reaction using first-principles simulation, and candidate elements that do not react with LCPO were extracted (Step S2). From this investigation, Sn was identified as one of the candidate elements that does not react with LCPO.

[0054] Next, machine learning was used to search for solid electrolyte compositions that contain the basic elements of the solid electrolyte and the candidate elements extracted as those that do not react with LCPO (step S3). Here, 37,000 battery material-related data were collected from a publicly available materials database (Materials Project) and used as training data for existing materials. On the other hand, materials that are made by combining simple oxides and are not listed in the database were used as training data for non-existent materials by AI. As learning descriptors, the average physical property values ​​of the elements that make up the crystal, such as ionic radius and electronegativity, by composition ratio and their standard deviation were used. Random forest was used for learning, and the hyperparameters were optimized by grid search. The prediction accuracy was evaluated by the prediction accuracy rate of existing materials and their cross-validation error. If no composition with low environmental impact existed (step S4), the candidate elements were changed and the processing from step S3 onwards was performed. Using the algorithm obtained by learning, Li was selected as a candidate composition that is highly likely to exist and has the highest Ge reduction amount. 1.4 Al 0.4 Sn 1.28 Ge 0.32 (PO4)3 was obtained.

[0055] From the obtained candidate compositions, a crystal structure was searched for using a genetic algorithm (step S5), and the Li-ion conductivity was confirmed by first-principles simulation (step S6). The search for the crystal structure was carried out in the following procedure (step S5). In the NASICON-type crystal structure, the positions of Li, P, and O were assumed to be unchanged, and Sn was assumed to be substituted into the lattice position of Ge and dissolved in solid solution. At this time, the lattice positions of Sn and Ge can be expressed as a one-dimensional array. 100 structures with different arrangements of Sn and Ge were randomly created, and the formation energy of each was calculated by first-principles calculation as the initial structure. Among them, 20 structures with the lowest formation energy were selected, and 100 new crystal structures were created using a genetic algorithm that replaces them by crossover and mutation, and the formation energy of each crystal structure was calculated by first-principles calculation. From these, 20 structures with the lowest formation energy were selected again, and 100 new crystal structures were created based on these to evaluate the formation energy. This operation was repeated for a maximum of 100 generations to search for the crystal structure with the lowest formation energy, i.e., the most stable crystal structure.

[0056] From the obtained crystal structure, reaction path analysis (NEB method) was performed by first-principles simulation to confirm the ion conductivity, and it was confirmed that the Li ion conductivity was improved compared to the conventional LAGP (step S6). If the Li ion conductivity did not improve (step S6), the composition was changed and the processing from step S5 onwards was performed. Alternatively, the composition was changed and the candidate elements were changed and the processing from step S3 onwards was performed. In addition, by looking at the energy difference between the raw oxide and the synthesized material from the obtained crystal structure, it was confirmed that the material was easy to synthesize. Furthermore, by calculating the X-ray diffraction pattern from the obtained crystal structure and comparing it with the X-ray diffraction pattern of the material after actual synthesis, it was possible to confirm whether the crystal structure was as expected.

[0057] Through this search procedure, LiSn y Ge 2-yThe material composition of (PO4)3 was obtained. At this time, a ratio of Sn composition to Ge composition of 4:1 was proposed as a composition that maintains a sufficiently high existence probability while reducing Ge. In order to further improve the ion conductivity of this composition, AI and simulation were used to study it, and the knowledge about existing solid electrolytes was also taken into consideration, and the Li 1+x Al x Sn y Ge 2-x-y The composition of (PO4)3 was obtained (Step S7). After actually producing the material and measuring its various properties, it was confirmed that the material can be synthesized stably, has Li-ion conductivity, electrochemical stability, and low reactivity with LCPO, and furthermore, by setting the ratio of Sn composition to Ge composition to 4:1, the amount of Ge, a rare element, can be reduced to one-fifth.

[0058] Next, Li 1+x Al x Sn y Ge 2-x-y An example of a solid-state battery using (PO4)3 will be described. Fig. 6 is a diagram for explaining an example of a method for manufacturing a solid-state battery. Fig. 6(A) shows a schematic cross-sectional view of a main part of an example of a battery element forming step. Fig. 6(B) shows a schematic cross-sectional view of a main part of an example of an external electrode forming step.

[0059] First, a battery element 10 is formed as shown in FIG. 6(A). The battery element 10 includes a positive electrode layer 11, a negative electrode layer 12, an electrolyte layer 13, and a cover layer 14. The positive electrode layer 11 and the negative electrode layer 12 are laminated so as to partially overlap each other with the electrolyte layer 13 interposed therebetween. The cover layer 14 is provided so as to cover a laminate including the positive electrode layer 11, the negative electrode layer 12, and the electrolyte layer 13 provided therebetween. The positive electrode layer 11 is provided so that a part of its side surface is exposed at one end surface 10a of the battery element 10, and the negative electrode layer 12 is provided so that a part of its side surface is exposed at the other end surface 10b of the battery element 10.

[0060] The electrolyte layer 13 includes a solid electrolyte. For example, an oxide-based solid electrolyte is used as the solid electrolyte of the electrolyte layer 13. Here, the above-mentioned Li 1+x Al x Sn y Ge 2-x-y (PO4)3 is used.

[0061] The positive electrode layer 11 includes a positive electrode active material, a conductive assistant, and a solid electrolyte. For example, an oxide-based solid electrolyte is used as the solid electrolyte of the positive electrode layer 11. For example, the solid electrolyte of the positive electrode layer 11 may be the same type of material as the solid electrolyte of the electrolyte layer 13, such as Li 1+x Al x Sn y Ge 2-x-y (PO4)3 is used. For example, LCPO or LiCoPO4 is used as the positive electrode active material of the positive electrode layer 11. For example, a conductive material such as carbon is used as the conductive assistant of the positive electrode layer 11.

[0062] The negative electrode layer 12 includes a negative electrode active material, a conductive assistant, and a solid electrolyte. For example, an oxide-based solid electrolyte is used as the solid electrolyte of the negative electrode layer 12. For example, the solid electrolyte of the negative electrode layer 12 may be the same type of material as the solid electrolyte of the electrolyte layer 13, such as Li 1+x Al x Sn y Ge 2-x-y (PO4)3 is used. For example, TiO2, Nb2O5, etc. are used as the negative electrode active material of the negative electrode layer 12. For example, a conductive material such as carbon is used as the conductive assistant of the negative electrode layer 12.

[0063] In the battery element 10, during charging, Li ions are conducted and taken up from the positive electrode layer 11 through the electrolyte layer 13 to the negative electrode layer 12, and during discharging, Li ions are conducted and taken up from the negative electrode layer 12 to the positive electrode layer 11 through the electrolyte layer 13. In the battery element 10, charging and discharging operations are realized by such Li ion conduction.

[0064] As the cover layer 14, for example, an insulating cover layer 14 is used which has a higher hardness than the solid electrolyte used in the positive electrode layer 11, the negative electrode layer 12, and the electrolyte layer 13, has low permeability to moisture, etc., and can realize good sealing. The insulating property of the cover layer 14 refers to a property that has no effect on Li ion conduction and electron conduction in the battery element or has a sufficiently low effect. For example, glass or ceramics is used for the cover layer 14.

[0065] In forming the battery element 10, pastes for forming the positive electrode layer 11, the negative electrode layer 12, the electrolyte layer 13, and the cover layer 14, each containing the material components as described above, are prepared. Then, each paste is laminated by printing to form a structure as shown in FIG. 6(A), or sheets formed from each paste by printing are laminated to form a structure as shown in FIG. 6(A). After lamination, thermocompression bonding, cutting, and the like may be performed. Then, a predetermined firing process is performed, that is, firing (degreasing or pre-firing) to remove organic components in the paste, and further firing (main firing) to sinter the solid electrolyte, glass, and the like. As a result, the battery element 10 having the structure shown in FIG. 6(A), that is, the battery element 10 including the positive electrode layer 11, the negative electrode layer 12, the electrolyte layer 13, and the cover layer 14, is formed.

[0066] In the firing process, the firing for sintering the solid electrolyte, glass, etc. is preferably carried out under temperature conditions of 500°C to 650°C. Under such temperature conditions, the reaction and decomposition of the positive electrode active material, LCPO, etc., can be effectively suppressed. 1+x Al x Sn y Ge 2-x-y A solid electrolyte represented by (PO4)3, in particular, Li, in which the Sn composition y and the Ge composition 2-xy=z are in the range of 0.13≦z / (y+z)≦0.33, and the Al composition x is in the range of 0.2≦x≦0.5. 1+x Al x Sn y Ge 2-x-y(PO4)3 is used. This allows the formation of a solid electrolyte that is dense and has good sinterability and high Li-ion conductivity, while suppressing the reaction with the positive electrode active material LCPO or the decomposition of LCPO. Therefore, the battery element 10 exhibiting excellent battery characteristics is formed.

[0067] After the battery element 10 is formed, the external electrode 20 and the external electrode 30 are formed as shown in FIG. 6(B). The external electrode 20 is formed on one end surface 10a of the battery element 10 so as to be connected to the positive electrode layer 11 exposed on the end surface 10a. The external electrode 20 functions as the positive electrode of the solid-state battery 1. The external electrode 30 is formed on the other end surface 10b of the battery element 10 so as to be connected to the negative electrode layer 12 exposed on the end surface 10b. The external electrode 30 functions as the negative electrode of the solid-state battery 1. Various conductive materials are used for the external electrode 20 and the external electrode 30. For example, the external electrode 20 and the external electrode 30 are formed by drying and hardening a conductive paste containing conductive particles of metals such as Ag, Cu, Ni, or carbon, or formed by depositing various metals using a sputtering method, a plating method, or the like.

[0068] By the above-described method, a solid-state battery 1 is manufactured, which includes a battery element 10 including a positive electrode layer 11, a negative electrode layer 12, an electrolyte layer 13, and a cover layer 14, as well as an external electrode 20 and an external electrode 30 provided on the end surface 10a and the end surface 10b, respectively.

[0069] In the solid-state battery 1, the solid electrolyte is Li 1+x Al x Sn y Ge 2-x-y A solid electrolyte represented by (PO4)3, in particular, Li, in which the Sn composition y and the Ge composition 2-xy=z are in the range of 0.13≦z / (y+z)≦0.33, and the Al composition x is in the range of 0.2≦x≦0.5. 1+x Al x Sn y Ge 2-x-y (PO4)3 is used. This allows the realization of a solid-state battery 1 that contains a dense solid electrolyte having high Li-ion conductivity and exhibits excellent battery characteristics.1+x Al x Sn y Ge 2-x-y (PO4)3 can reduce the content of rare and expensive Ge compared to conventional LAGP, which allows the realization of a solid-state battery 1 with excellent battery characteristics at low cost. [Explanation of symbols]

[0070] 1 solid state battery 10 Battery elements 10a, 10b end face 11 Positive electrode layer 12 Negative electrode layer 13 Electrolyte layer 14 Cover Layer 20, 30 external electrode

Claims

1. A solid electrolyte comprising Li, Al, Sn, Ge and P, having a polyphosphate skeleton and Li ion conductivity, wherein the Ge composition is smaller than the Sn composition.

2. Composition formula Li 1+x A x Sn y Ge 2-x-y (P.O. 4 ) 3 The solid electrolyte according to claim 1, wherein the Sn composition y and the Ge composition 2-x-y=z satisfy the relationship 0.13≦z / (y+z)≦0.

33.

3. Composition formula Li 1+x A x Sn y Ge 2-x-y (P.O. 4 ) 3 The solid electrolyte according to claim 1, wherein the Sn composition y and the Ge composition 2-x-y=z satisfy the relationship z / (y+z)=0.

2.

4. Composition formula Li 1+x A x Sn y Ge 2-x-y (P.O. 4 ) 3 The solid electrolyte according to claim 1, 2, or 3, wherein the Al composition x is in the range of 0.2≦x≦0.

5.

5. A solid-state battery comprising the solid electrolyte according to claim 1 .

6. The solid electrolyte and the positive electrode active material Li 2 CoP 2 O 7 or LiCoPO 4 The solid-state battery of claim 5 .

7. 2. A method for producing a solid-state battery including the solid electrolyte according to claim 1, comprising the step of firing the solid electrolyte at a temperature of 500° C. or more and 650° C. or less.

Citation Information

Patent Citations

  • All-solid battery, and method for manufacturing all-solid battery

    JP2015069843A